Biofeedback: An Important but Often-Ignored Ingredient in Psychotherapy. (March 2017) - Lehrer, Paul
Although evidence supports the efficacy of biofeedback for treating a number of disorders and for enhancing performance, significant barriers block both needed research and payer support for this method. Biofeedback has demonstrated effects in changing psychophysiological substrates of various emotional, physical, and psychosomatic problems, but payers are reluctant to reimburse for biofeedback services. A considerable amount of biofeedback research is in the form of relatively small well-controlled trials (Phase II trials). This article argues for greater payer support and research support for larger trials in the "real life" clinical environment (Phase III trials) and meta-analytic reviews.